'In this house we believe in fairness and kindness': Post-liberation politics in Australia's same-sex marriage postal survey. (June 2020) - Thomas, Amy; McCann, Hannah; Fela, Geraldine
In December 2017, Australia legalized same-sex marriage (SSM), following a 13-year ban and a drawn-out postal survey on marriage equality that saw campaigners mobilize for a 'Yes' vote on a non-binding poll. Through a discourse analysis of the Yes and No campaigns' television and online video advertisements, we demonstrate how the Yes campaign was symptomatic of what we call a 'post-liberation' approach that saw SSM as the last major hurdle for Lesbian, Gay, Bisexual, Transgender, Intersex and Queer (LGBTIQ) politics. While the No campaign linked SSM to gender fluidity, transgender identity, and sex education programmes, in contrast the Yes campaign limited itself to narratives around love and marriage. In not attending to the link between sex, gender and sexuality, the Yes campaign narrowed the possibilities of the debate, preserving existing White heteronormative expectations of gender and sexuality. We contrast the debate that unfolded during the postal survey to the Australian Gay Liberation movement of the 1970s, the latter of which was able to successfully and radically challenge similarly homophobic campaigns. Rather than relying on 'palatable' or mainstream ideas of equality, love and fairness, Gay Liberation in Australia embraced the radical potential of LGBTIQ activism and presented a utopian, optimistic vision of a transformed future. Here we suggest that we can learn from the history of campaigns around sexuality, to understand what was 'won' in the SSM debate, and to better develop strategies for change in the future.